ANALISIS DESKRIPTIF CROSS-SECTIONAL KONDISI KESEHATAN DAN TINGKAT IMUNISASI WILAYAH PAPUA BARAT - Fitrah Sarah Ramadhani (Dian Nuswantoro Semarang, 2019)
Papua Barat is a province which had the third lowest life expectancy among other provinces in 2017. This situation showed that health condition in Papua Barat was way lower than other provinces in Indonesia. A method which was believed can improve health condition in an area was to increase the immunization for babies and children under five years (balita) in that area. The objective of this study was to describe health condition and the rate of children who had immunization in regions in Papua Barat in 2017, also to describe the relation between those two variables. This study used secondary data, collected by Statistics of Papua Barat. Descriptive Analysis was used in this study. Results showed that health condition tended to have positive association with immunization rate in most regions in Papua Barat. Moreover, health condition and immunization rate in first established regions in Papua Barat was relatively higher than the rest of regions. Conclusion out of the results was most regions in Papua Barat tended to have a better health condition along with higher rate of immunization.